A Study On The Effects of Breathing Cycle Training Technique Together With Dzikr Recitation Towards Achievement of Students’ HRV - Muhammad Nubli, Abdul Wahab; Azham, Abdul Rahman (Foundation of Computer Science, 2015)
This experiment put emphasis on slow breathing exercise while reciting dzikr. The HRV readings of the students involved were recorded throughout the experiment. Slow breathing or resonant breathing exercises have been proven to be able to lower the heart rate and thus increase the HRV. Recitation of ‘dzikr’ (Islamic recitation) is known to have positive impacts towards emotion. When properly recited, ‘dzikr’ could bring calmness to the mind and emotions. An emotion at peace could then bring better results from any actions. Forty secondary school students with behavioral problems were chosen to undergo a biofeedback procedure that incorporated ‘dzikr’ recitation together with slow breathing technique. ‘Dzikr’ intervention enabled the students to make changes themselves using the technique of "Heart Rate Variability" (HRV). Students were instructed to perform resonant breathing while chanting slowly and loudly of the ‘la ilaha illa Allah’ ‘dzikr’. The study found that students who successfully completed the resonant breathing and ‘dzikr’ training were able to make changes within themselves. The students had successfully achieved the change score "HRV Coherence" of the VLF spectrum of LF and HF spectrum conditions. The study had found that this technique was very effective and suitable to be implemented to assist students in making behavioral changes. This technique can be used in schools to help improve the students’ behavior and thus enabling education programs to be implemented successfully.